Differential effects of strength training and testosterone treatment on soluble CD36 in aging men: Possible relation to changes in body composition. (17th November 2015) - Glintborg, Dorte; Christensen, Louise L.; Kvorning, Thue; Larsen, Rasmus; Højlund, Kurt; Brixen, Kim; Hougaard, David M.; Handberg, Aase; Andersen, Marianne
Abstract : Purpose . We measured soluble CD36 (sCD36) and body composition to determine the effects of testosterone treatment (TT) and/or strength training (ST) on cardiovascular risk in men with low normal testosterone levels. Methods . Double-blinded, placebo-controlled study in 54 men aged 60–78 years with bioavailable testosterone < 7.3 nmol/L and waist > 94 cm randomized to TT (gel, 50–100 mg/day, n = 20), placebo ( n = 18) or ST ( n = 16) for 6 months. Moreover, the ST group was randomized to TT (ST + TT, n = 7) or placebo (ST + placebo, n = 9) after 3 months. Outcomes . sCD36, total and regional fat mass were established by Dual X-ray absorptiometry and magnetic resonance imaging. Data are presented as median (quartiles). Kruskal-Wallis and Mann-Whitney tests were performed on delta values at 0, 3 and 6 months. Results . ST + placebo decreased sCD36 levels by 21% [from 0.80 (0.68–1.22) to 0.63 (0.51–0.73) rel. units] vs. TT and vs. placebo ( p < 0.05). ST + placebo did not change bioavailable testosterone and lean body mass. Fat mass measures significantly improved during ST + placebo, ST + TT, and TT vs. placebo. During ST + placebo, delta sCD36 was associated with delta total fat mass ( r = 0.81) and delta central fat mass ( r = 0.84). Conclusions . Compared to testosterone treatment, six months of strength training reduced sCD36 levels suggesting decreased cardiovascular risk, possibly due to a reduction in central fat mass.